Stories of Change: Rwanda: Understanding the drivers of stunting reduction among Rwandan children from 2005 to 2015 - Ramani, Gayathri V.; Heckert, Jessica; Go, Ara; Iruhiriye, Elyse; Niyongira, Emmanuel; Olney, Deanna K. (International Food Policy Research Institute, 2019)
Despite significant progress, childhood stunting is still a serious public health concern in Rwanda. To make further progress in reduc-ing child stunting it is essential to understand the context-specific drivers of stunting to devise strategies to address these causes. The primary objective of this study was to assess the drivers of change in stunting reduction among children 0-59 months of age between 2005 and 2015 in Rwanda.